Quantitative analysis of food waste from wholesale to households in Colombo, Sri Lanka - Jayathilake, Nilanthi; Aheeyar, Mohamed M. M.; Drechsel, Pay; Bucatariu, C. (Food and Agriculture Organization of the United Nations, 2023)
Currently, in Sri Lanka, strategies to address FW prevention and reduction are being considered by different state and non-state stakeholders. However, in the current scenario, solutions for FW are mostly addressing (bio-)waste management. Quantifying FW is of paramount importance in understanding the magnitude and socio-economic as well as environmental impacts of the problem. A good understanding of the availability and quality of FW data is a prerequisite for tracking progress on reduction targets, analyzing environmental impacts, and exploring mitigation strategies for FLW (Xue et al., 2019). FW quantification aims at creating a robust evidence base for developing strategies, action plans, and policies towards FW prevention, reduction, and management as well as guide prioritization of actions, evaluation of solutions, and monitoring progress (CEC, 2019).